Jealousy - The Green-Eyed Monster and Its Relationship with Depression, and Personality. Causal or Coincidental? - Thomson, Wendy (British Journal of Healthcare and Medical Research, 2025)
This research is an example of theory and therapeutic practice converging. Using experiential and subjective ideation gained as a therapist and then as a researcher to test and evaluate hypotheses. Furthermore, this research is a continuation of Thomson (2019) and earlier research Thomson (1996, 2011) which investigated the nature and consequences of a depressive illness. There is no one accepted theory of depression. To extend the research profile a questionnaire : the Self-Defeating Quotient; SDQ, (2016, 2017). The SDQ is an anonymous self administered questionnaire. The bottom-up approach was used to start with the patients themselves by using the SDQ to obtain data concerning the underlying factors in a depressive illness. Jealousy and neuroticism were found to be significantly correlated with a depressive illness... Results: Jealousy was found to be significantly correlated with depression. Factor analysis played a significant but unexpected part in defining the emotion jealousy in a cohort of depressed patients. Additional variables found to be associated with jealousy were family, family time, and education: The implication being that these foundational variables may have causative connections with jealousy and depression. The inference for treatment is briefly discussed alongside the implications following previous findings on the mortality of a depressive illness. Summary: The results found in this pilot study ideally justify further verification using a larger sample of depressed patients.